Hb lynwood [a107(G14) (-T) (a2) HBA2:c.323delT)] in conjunction with the a3.7 deletion produces a moderately severe a-thalassemia phenotype - Finlayson, J.; Ghassemifar, Reza; Holmes, P.; Grey, D.; Newbound, C.; Pell, N.; Jennens, M.; MacAulay, C.; Greenwood, L.; Beilby, J. (2011)
We describe a novel frameshift mutation associated with an a-thalassemia (a-thal) phenotype in a patient of Sudanese origin investigated for persistent microcytosis. In addition to the a3.7 deletion, a novel mutation on the a2 gene was detected: HBA2:c.323delT. This mutation causes a frameshift at codon 107 of the a2 gene. The result is a disturbed amino acid sequence for the following 24 amino acids, and a premature termination codon at position 132. © 2011 Informa Healthcare USA, Inc.